2022
DOI: 10.1002/icd.2349
|View full text |Cite
|
Sign up to set email alerts
|

Social support and end‐of‐semester depression, burnout, and adjustment in students making the transition to university

Abstract: Nearly 40% of Canadian university students are depressed. However, strong social support may mitigate adverse outcomes for some. This study examined: (1) If students who showed initial depression were more likely to experience poorer end‐of‐semester well‐being (continued depressive symptoms, burnout, and poor social and academic adjustment); and (2) if social support was a moderator for initial depression effects on poorer end‐of‐semester well‐being. Participants (N = 461) were first‐time first‐year undergradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…49 In addition, a sense of social support helps students identify and maintain learning goals in complex learning environments, allowing them to experience less academic distress and reducing their complaining emotions, which reduces their symptoms of learning burnout such as anxiety, stress, and overwhelm. 84 A number of studies have confirmed the impact of teachers' social support on university students' motivation and burnout. A study of 1048 Spanish university students shows that a teacher-supported teaching style is beneficial for motivating students to learn, helping students acquire knowledge in a reflexive way, and improving their self-esteem, confidence, and enthusiasm for learning.…”
mentioning
confidence: 99%
“…49 In addition, a sense of social support helps students identify and maintain learning goals in complex learning environments, allowing them to experience less academic distress and reducing their complaining emotions, which reduces their symptoms of learning burnout such as anxiety, stress, and overwhelm. 84 A number of studies have confirmed the impact of teachers' social support on university students' motivation and burnout. A study of 1048 Spanish university students shows that a teacher-supported teaching style is beneficial for motivating students to learn, helping students acquire knowledge in a reflexive way, and improving their self-esteem, confidence, and enthusiasm for learning.…”
mentioning
confidence: 99%